Evaluasi Penerapan Patient Safety dalam Pemberian Obat di Wilayah Kerja Puskesmas Kasihan II Kabupaten Bantul Yogyakarta - Anggi Napida Anggraini; Fatma Siti Fatimah (Alma Ata University Press, 2015)
Patient safety is the absence of the danger posed to the patient can be prevented during the process of health care. One of the indicators of patient safety in pharmacy practice is the principle of the drug, this using the 6 principles of drug administration. Research using a mix method, this research occured in Puskesmas of Kasihan II on October 5-28, 2015. The respondents in this study were 2 pharmacists, patient and the head of the health center. Application of patient safety in drug delivery based on 6 principles correctly, showing 100% true with principles and expired, 78,5% true principles patient, 63,7% right drug, right dose of 94,1% and 25,5% correct information. Based on qualitative analysis, the application of patient safety based on 6 principles of drug administration were obtained, the officer checks the identity of the patient, adjust the dose, adjusting the recipe, provide drug-related information provided to the patient. Problems derived from the application of the 6 principles of drug delivery was 6 reciper identified were given much more than the actual dose, no places to store drugs that have expired, an imbalance between the number of patients pharmacist. Advice and hope that can be given is the addition of human resources in pharmacy and provide room for storing medicines that have expired.